A Study of the Speed of the Sabit Kick Among Pencak Silat Athletes at Pat Ban Bu in Padang - Meisarah Meisarah; Roma Irawan; Juanda Juanda; Ardo Okilanda (Jurnal Gladiator, 2026)
The background of this study is the lack of objective data on the speed of the sickle kick among pencak silat athletes at PAT BAN BU in Padang, even though such information is crucial for evaluating performance and designing training programs. The objective of this study is to determine the speed of the sickle kick among pencak silat athletes at Pat Ban Bu in Padang. The research method employed a descriptive quantitative approach. The population consisted of 25 athletes, and the entire population was selected as the sample using total sampling. The instrument used was a crescent kick speed test, in which participants performed as many kicks as possible within 10 seconds, using both the right and left legs. Data analysis employed descriptive statistics (mean, minimum, maximum, and percentage) in accordance with established assessment standards. The results of the study showed that for right-foot kicks, the average for female athletes was 21 and for male athletes 21.85; the majority of female athletes (67%) and male athletes (85%) fell into the “good” category. For left-foot kicks, the average for female athletes was 20 and for male athletes 21.77; the “good” category was achieved by 75% of female athletes and 69% of male athletes. No athletes were found in the “poor” or “very poor” categories. In conclusion, the speed of the crescent kicks by PAT BAN BU athletes in Padang City is classified as good.